2020
DOI: 10.3390/ijerph17020436
|View full text |Cite
|
Sign up to set email alerts
|

Activated Sludge Microbial Community and Treatment Performance of Wastewater Treatment Plants in Industrial and Municipal Zones

Abstract: Controlling wastewater pollution from centralized industrial zones is important for reducing overall water pollution. Microbial community structure and diversity can adversely affect wastewater treatment plant (WWTP) performance and stability. Therefore, we studied microbial structure, diversity, and metabolic functions in WWTPs that treat industrial or municipal wastewater. Sludge microbial community diversity and richness were the lowest for the industrial WWTPs, indicating that industrial influents inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 49 publications
(59 reference statements)
3
36
0
Order By: Relevance
“…Previous studies reported that WWTPs was dominated by Bacteroidetes aerobic carbon degraders [49] dominant in aerated sludges [50]. Indeed, the FS samples contained a dominance of the Proteobacteria (38.9%), the Bacteroidetes (19.4%), The Actinobacteria (10.2%), the Chloroflexi (6.6%), and Planctomycetes (6.2%) as reported by [51].…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies reported that WWTPs was dominated by Bacteroidetes aerobic carbon degraders [49] dominant in aerated sludges [50]. Indeed, the FS samples contained a dominance of the Proteobacteria (38.9%), the Bacteroidetes (19.4%), The Actinobacteria (10.2%), the Chloroflexi (6.6%), and Planctomycetes (6.2%) as reported by [51].…”
Section: Discussionmentioning
confidence: 59%
“…However, in the case of diversity indices for Archaea their values were similar for samples taken both upstream and downstream the effluent discharge point. According to the indices values the investigated samples had high microbial diversity compared with the literature data [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 72%
“…Here, we observed significant changes in the microbial composition between the fresh activated sludge collected from the municipal sewage treatment plant and the activated sludge fed with synthetic sewage afterwards. Changes in the bacterial community of WWTPs can be affected by several factors such as the composition of the wastewater [ 31 , 32 , 33 ], the temperature [ 34 ], gas/water ratio [ 34 , 35 ], and hydraulic retention time [ 32 ]. In the present study a controlled simulated treatment plant was used, in which those factors remained stable during the experiment and can be excluded as the reason for the observed changes.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above, one the main reasons for the significant change of the microbial structure in the first days of the laboratory experiment is the composition of the synthetic sewage which differs from municipal wastewater. Yang et al [ 31 ] analyzed the composition of industrial and municipal wastewater and determined low concentrations of phenol, formaladehyde, aniline, surfactants, and chlorobenzene in the municipal wastewater. This indicates a much higher diversity of carbon sources compared to the synthetic sewage which only contains peptone, meat extract, and urea which can affect the composition of the microbial community.…”
Section: Discussionmentioning
confidence: 99%